No Soviet Power, No Armenian Nation: Reason for State and Nation Building Under Imperial Conditions (KULT_online, 2013)
In Armenia a retrospective look at the Soviet past leads to the conclusion that building an Armenian nation after 1945 had to take place on essentially hybrid foundations. Considering this Maike Lehmann describes the principles that determined this process under Soviet circumstances at the periphery. Her dissertation offers a historical research of discourses which dealt with specifically Armenian "national" questions and discusses the embedding of these issues into narratives focusing all in all on a (Soviet) supranational integration. A result of these contradictory developments was the manifestation of a Soviet nation in the true sense of the word. The Armenian society has been shaped by these structures up to the present day.